Negative electrode sheet and preparation method thereof, secondary battery, battery module, battery pack and device
By setting a multi-layer structure active material layer on the negative electrode sheet of the lithium-ion secondary battery and controlling its particle size, the problem of insufficient battery energy density and fast charging performance is solved, and the high energy density and fast charging capability are achieved.
Patent Information
- Application Number
- CN202080102408.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-12-28
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2040-12-28
AI Technical Summary
Lithium-ion secondary batteries are difficult to meet the needs of users in terms of energy density and charge and discharge rate, especially in fast-paced production and life.
By providing the first active material layer and the second active material layer on the current collector and controlling its particle size, the lithium ion embedding/detachment amount and the migration rate of lithium ions with electrons are improved, thereby improving the energy density and fast charging performance of the battery.
It achieves the improvement of the fast charging performance of the battery while maintaining high energy density, and significantly improves the overall energy density and charge and discharge rate of the battery.
Smart Images

Figure CN115917780B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of electrochemical technology. More specifically, the present application relates to a negative electrode sheet and a preparation method thereof, a secondary battery, a battery module, a battery pack and an electrical device. Background Art
[0002] With the rapid development of the new energy field, secondary batteries, especially lithium-ion secondary batteries, are widely used in various large-scale power devices, energy storage systems and various consumer products due to their excellent charging and discharging chemical properties, no memory effect and low environmental pollution.
[0003] In recent years, the widespread popularity of power-consuming devices such as smartphones and electric vehicles has enabled the widespread use of lithium-ion secondary batteries. However, in the fast-paced production and life, some electrochemical properties of lithium-ion secondary batteries, especially in terms of battery energy density and charge and discharge rate, do not meet the needs of users, which puts higher requirements on the development of lithium-ion secondary batteries. For lithium-ion secondary batteries, the negative electrode is the place where lithium ions are embedded and released during the battery charging and discharging process, which has a significant impact on the electrochemical properties of lithium-ion secondary batteries.
[0004] Therefore, it is urgent to develop a secondary battery with high energy density and fast charging capability. Summary of the invention
[0005] In view of the problems existing in the background technology, the present application provides a negative electrode plate and a preparation method thereof. The secondary battery prepared by the negative electrode plate of the present application has a high battery energy density and a high charge and discharge rate, and has excellent fast charging performance while having a high energy density.
[0006] One object of the present application is to provide a negative electrode sheet with improved charge and discharge rates and a method for preparing the same.
[0007] An object of the present application is to provide a lithium ion secondary battery with high energy density and a method for preparing the same.
[0008] The inventors have discovered that one or more of the above-mentioned purposes can be achieved by adopting the technical solution of the present application.
[0009] A first aspect of the present application provides a negative electrode sheet, comprising a current collector and a first active material layer and a second active material layer sequentially disposed on at least one surface of the current collector;
[0010] The first active material layer includes a first negative electrode active material, and the particle size of the first negative electrode active material satisfies the relationship shown in formula (I): 0.02≤A1=(D n 10)1 / (D v 50)1≤0.2, formula (I);
[0011] Wherein, the second active material layer includes a second negative electrode active material, and the particle size of the second negative electrode active material satisfies the relationship shown in formula (II): 0.02≤A2=(Dn10)2 / (Dv50)2≤0.3, formula (II);
[0012] Furthermore, in formula (I) and formula (II), A1 and A2 satisfy 1<A2 / A1<2.5.
[0013] The negative electrode sheet provided in the first aspect of the present application has a secondary battery prepared therefrom with excellent fast charging performance and energy density. The present application provides a first active material layer and a second active material layer on the current collector to comprehensively improve the amount of lithium ion insertion / extraction, as well as the migration rate of lithium ions and electrons, so that the overall energy density and charge and discharge rate of the battery are significantly improved.
[0014] At the same time, the present application also indirectly regulates the relative porosity of the first active material layer and the second active material layer by regulating the particle size of the active material in the first active material layer and the second active material layer, and then regulates the embedding / extraction amount of lithium ions on the negative electrode sheet and the migration rate of lithium ions and electrons by changing the porosity, thereby improving the battery energy density and fast charging capability. After a lot of research and experiments, when the particle size of the first active material and the second active material on the negative electrode sheet simultaneously satisfies 0.02≤A1≤0.2, 0.02≤A2≤0.3 and 1<A2 / A1<2.5, the secondary battery prepared from the negative electrode sheet has both high energy density and high charge and discharge rate.
[0015] In any embodiment of the present application, optionally, on the negative electrode sheet of the present application, the first negative electrode active material (D v 50)1 is 12μm~20μm, and can be optionally 14μm~18μm.
[0016] In any embodiment of the present application, optionally, on the negative electrode sheet of the present application, the second negative electrode active material (D v 50)2 is 8μm~17μm, and can be optionally 10μm~15μm.
[0017] The negative electrode plate provided by the present application has a first active material layer that improves the overall energy density of the battery more significantly than improving the fast charging capability of the battery; and the second active material layer improves the overall fast charging capability of the battery more significantly than improving the energy density of the battery. The present application achieves the above purpose by regulating the particle size of the first negative electrode active material and the second negative electrode active material particles. The particle size range of the negative electrode active material provided by the present application can significantly improve the energy density and fast charging capability of the battery. That is, when the average particle size (D vWhen the average particle size of the second negative electrode active material (D v When 50)2 is 12μm to 20μm, the secondary battery as a whole has a significantly improved charge and discharge rate, which significantly improves the fast charging capability of the battery.
[0018] In any embodiment of the present application, optionally, the first negative electrode active material (D n 10) 1 is 0.5 μm to 2 μm, and can be 0.8 μm to 1.8 μm; the second negative electrode active material (D n 10)2 is 0.5μm~2μm, and can be optionally 0.8μm~1.8μm.
[0019] After extensive research and experimentation, D n The value of 10 can regulate the porosity of the negative electrode active material and has a significant effect on the conduction of lithium ions and electrons during battery charging and discharging. n 10 can significantly improve the energy density and fast charging capability of the battery, that is, when the first negative electrode active material (D n 10)1 is 0.5 μm to 2 μm, and the second negative electrode active material (D n 10) When 2 is 0.5 μm to 2 μm, the secondary battery as a whole has significantly improved charge and discharge rates and energy density, which significantly improves the battery's power durability and fast charging capability.
[0020] In any embodiment of the present application, optionally, the second negative electrode active material (D v 50)2 is less than the first negative electrode active material (D v 50)1, and (D v 50)1 and (D v 50)2 is not less than 3μm.
[0021] After a lot of research and experiments, when the first negative electrode active material (D v 50)1 is greater than the first negative electrode active material (D v 50)2, the second negative electrode active material layer has a relatively high OI value. The relatively high OI value of the second negative electrode active material layer is conducive to improving the overall bonding strength of the negative electrode sheet, while also ensuring that the second active material layer has a higher porosity and improving the fast charging capability of the negative electrode sheet.
[0022] In any embodiment of the present application, optionally, the thickness T1 of the first active material layer is 20 to 60 μm, and optionally 25 to 40 μm.
[0023] The negative electrode plate provided in the present application has a first active material layer thereon which is mainly used to improve the overall energy density of the battery. Therefore, its suitable thickness range is conducive to improving the overall power durability of the battery.
[0024] In any embodiment of the present application, optionally, the thickness T2 of the second active material layer is 25 to 70 μm, and optionally 30 to 45 μm.
[0025] The negative electrode plate provided in the present application has a second active material layer thereon which is mainly used to increase the overall porosity of the negative electrode plate, thereby increasing the migration rate of lithium ions and electrons. Therefore, its appropriate thickness range is beneficial to increasing the overall charge and discharge rate of the battery and improving the fast charging capability of the battery.
[0026] In any embodiment of the present application, optionally, the thickness T2 of the second active material layer is not less than the thickness T1 of the first active material layer.
[0027] If the thickness T2 of the second active material layer is less than the thickness T1 of the first active material layer, the overall pore content of the electrode will be reduced and the high-rate charging capacity will deteriorate; if the thickness of the second electrode layer is much greater than the thickness of the first electrode layer, the overall compaction of the electrode will be small, which will deteriorate the battery energy density.
[0028] In any embodiment of the present application, optionally, a ratio T2 / T1 of a thickness T2 of the second active material layer to a thickness T1 of the first active material layer is 1.1 to 2.4.
[0029] In any embodiment of the present application, optionally, the product of T2 / T1 and A2 / A1 satisfies 1.1≤(T2 / T1)×(A2 / A1)≤2.9.
[0030] After a lot of research and experiments, the parameter (T2 / T1)×(A2 / A1) can actually characterize the degree of influence of the relative size of the thickness of the first active material layer and the second active material layer and the relative size of their porosity on battery performance. When the product of T2 / T1 and A2 / A1 satisfies: 1.1≤(T2 / T1)×(A2 / A1)≤2.9, the thickness distribution of the negative electrode sheet is reasonable as a whole, the pore distribution is reasonable, and the battery has both high energy density and fast charging performance.
[0031] In any embodiment of the present application, optionally, the first negative electrode active material includes graphite, and optionally the first negative electrode active material is composed of pure graphite; and / or, the second negative electrode active material includes graphite and silicon, and optionally the second negative electrode active material is composed of graphite and silicon.
[0032] In any embodiment of the present application, optionally, in the second negative electrode active material, the content of silicon converted into silicon monoxide accounts for 1 to 20% of the second negative electrode active material, and optionally 2 to 15% by mass.
[0033] The first negative electrode active material contains graphite, and the first active material layer has a low porosity content, which helps to improve the overall compaction performance of the electrode sheet and increase the energy density of the battery.
[0034] The negative electrode plate provided in the present application has a high pore content in the second active material layer, which is not conducive to the improvement of the compaction density of the second negative electrode active material to a certain extent. Distributing silicon in the second active material layer significantly increases the gram capacity of the second active material layer, so that more and faster lithium ions are embedded or removed during the high-rate charge and discharge process of the battery, and the overall fast charging capability and power durability of the battery are significantly improved. However, excessive silicon will cause rapid decay of the battery cycle life, so there is a suitable range for the silicon oxide content, that is, the silicon oxide content accounts for 1 to 20% of the total content of the second negative electrode active material.
[0035] In any embodiment of the present application, optionally, the graphite in the first and second negative electrode active materials is selected from artificial graphite, and the artificial graphite is primary particles and / or secondary particles;
[0036] Optionally, the graphite in the first negative electrode active material is a primary particle, and the graphite in the second negative electrode active material is a secondary particle.
[0037] The first negative electrode active material is primary particles, which helps to improve the overall compaction performance of the pole piece and increase the battery energy density. The second layer of graphite uses secondary particles, which are formed by the aggregation of primary particles, which helps to increase the pores between particles, effectively improve the material's liquid retention capacity, and provide more liquid phase carriers for the transmission of lithium ions in the negative electrode active material to increase the lithium ion transmission rate, thereby increasing the battery charge and discharge rate.
[0038] The first aspect of the present application provides a method for preparing a negative electrode sheet, comprising the following steps:
[0039] Step S1: providing a first negative electrode active material, wherein the particle size of the first negative electrode active material satisfies the relationship shown in formula (I): 0.02≤A1=(Dn10)1 / (Dv50)1≤0.2, formula (I);
[0040] Step S2: preparing a slurry A containing the first negative electrode active material;
[0041] Step S3: providing a second negative electrode active material, wherein the particle size of the second negative electrode active material satisfies the relationship shown in formula (II): 0.02≤A2=(Dn10)2 / (Dv50)2≤0.3, formula (II);
[0042] Step S4: preparing a slurry B containing a second negative electrode active material;
[0043] Step S5: applying slurry A on at least one surface of the current collector to form a first active material layer; applying slurry B on the surface of the first active material layer to form a second active material layer; then drying, cold pressing, slitting, and die-cutting to obtain a negative electrode sheet; wherein A1 and A2 satisfy 1<A2 / A1<2.5.
[0044] In any embodiment of the present application, optionally, in step S1, the preparation of the first negative electrode active material is sequentially carried out through the processes of raw material screening, shaping and grading, graphitization, and demagnetization and screening to obtain an average particle size (D v 50)1 A first negative electrode active material with a diameter of 12 μm to 20 μm.
[0045] In any embodiment of the present application, optionally, in step S3, the second negative electrode active material includes graphite and silicon; wherein the preparation of graphite is sequentially carried out through the processes of raw material screening, shaping and grading, granulation, graphitization, carbonization, and demagnetization and screening; the preparation of silicon is carried out through the process of carbon coating; the above-mentioned graphite and the above-mentioned silicon are mixed to obtain an average particle size (D v 50)2 The second negative electrode active material is between 8μm and 17μm.
[0046] In any embodiment of the present application, optionally, in step S2 and step S4, the conductive agent includes one or more of conductive carbon black, graphene, vapor-generated carbon fiber VGCF and carbon nanotubes;
[0047] Optionally, the added mass ratio of the negative electrode active material, the conductive agent, the binder and the thickener is negative electrode active material: conductive agent: binder: thickener = 50-200: 1: 0.8-4: 0.5-1.5.
[0048] In any embodiment of the present application, optionally, in step S4, the second negative electrode active material includes silicon and graphite, and the conductive agent includes graphene or carbon nanotubes;
[0049] Optionally, the mass addition ratio of silicon to graphene or silicon to carbon nanotubes is 100-200:1.
[0050] The second aspect of the present application provides a method for preparing a negative electrode sheet, which has a simple preparation process and low raw material cost, and is conducive to large-scale industrialization. The negative electrode sheet prepared according to the method of the present application is an indispensable raw material for preparing a battery with both fast charging capability and high energy density.
[0051] The third aspect of the present application provides a secondary battery, comprising the negative electrode sheet of the first aspect of the present application or the negative electrode sheet prepared according to the method of the second aspect of the present application.
[0052] A fourth aspect of the present application provides a battery module, comprising the secondary battery of the third aspect of the present application.
[0053] A fifth aspect of the present application provides a battery pack comprising one or more of the secondary battery of the third aspect of the present application or the battery module of the fourth aspect of the present application.
[0054] The sixth aspect of the present application provides an electrical device, comprising one or more of the secondary battery of the third aspect of the present application, the battery module of the fourth aspect of the present application, or the battery pack of the fifth aspect of the present application; the secondary battery or battery module or battery pack can be used as a power source for the electrical device or an energy storage unit for the electrical device.
[0055] The present application provides a negative electrode sheet, which is obtained by providing a first active material layer and a second active material layer, and by regulating the particle size of the first active material and the particle size of the second active material. When the particle size of the first active material and the second active material on the negative electrode sheet simultaneously satisfies 0.02≤A1≤0.2, 0.02≤A2≤0.3, and 1<A2 / A1<2.5, a negative electrode sheet system with high energy density and high kinetics is obtained, and the secondary battery prepared from the negative electrode sheet has both high energy density and fast charging capability. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 It is a scanning electron microscope image of the first negative electrode active material according to one embodiment of the present application.
[0057] Figure 2 This is a scanning electron microscope image of the graphite component in the second negative electrode active material according to one embodiment of the present application.
[0058] Figure 3 This is a scanning electron microscope image of the silicon component in the second negative electrode active material according to one embodiment of the present application.
[0059] Figure 4 It is a scanning electron microscope image of the second negative electrode active material according to one embodiment of the present application.
[0060] Figure 5 This is a scanning electron microscope image of the negative electrode sheet according to one embodiment of the present application.
[0061] Figure 6 It is a charge and discharge rate-negative electrode potential curve diagram of a secondary battery prepared from the negative electrode sheet in Example 1 of the present application under different SOC states.
[0062] Figure 7 is a schematic diagram of a secondary battery according to one embodiment of the present application.
[0063] Figure 8 yes Figure 7 An exploded view of a secondary battery according to an embodiment of the present application is shown.
[0064] Fig. 9 is a schematic diagram of a battery module according to an embodiment of the present application.
[0065] Fig.10 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0066] Fig.11 yes Fig.10 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0067] Fig.12 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0068] Description of reference numerals:
[0069] 1 battery pack
[0070] 2 upper box
[0071] 3 lower cabinets
[0072] 4 battery modules
[0073] 5. Secondary battery
[0074] 51 Shell
[0075] 52 electrode assembly
[0076] 53 Top cover assembly DETAILED DESCRIPTION
[0077] Below, the negative electrode sheet and its manufacturing method, positive electrode sheet, secondary battery, battery module, battery pack and electric device of the present application are described in detail with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0078] For simplicity, the present application specifically discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value itself can be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0079] In the fast-paced production and life, some electrochemical properties of lithium-ion secondary batteries, especially in terms of energy density, charge and discharge rate, etc., cannot meet the needs of users, which puts higher requirements on the design and development of lithium-ion secondary batteries. Among them, the modification of the negative electrode is an important way to improve the battery energy density and charge and discharge rate.
[0080] Although the mechanism is not clear, the applicant unexpectedly discovered that the fast charging ability of the battery is significantly correlated with the pore distribution of the negative electrode plate. The more pores in the negative electrode plate and the more reasonable the distribution, the better the wettability of the electrolyte to the negative electrode active material, and the stronger the electrolyte retention ability of the plate. As a result, the conduction resistance of lithium ions between the negative electrode plate and the electrolyte in the present application is significantly reduced, and the transmission path of lithium ions in the negative electrode plate is significantly reduced, thereby significantly improving the charge and discharge capacity of the secondary battery at a high rate.
[0081] However, the existing methods for evaluating the porosity of the pole piece have great limitations. They are greatly affected by the pole piece processing and whether the powder is shed, and it is difficult to intuitively evaluate the overall porosity of the pole piece. In addition, the overall porosity of the pole piece is greatly affected by the thickness of the coated active material. The existing methods for evaluating the porosity of the pole piece cannot be applied to the case where there are active materials of different thicknesses on the current collector, especially when the second layer is thicker than the first layer in the case of double-layer coating.
[0082] Based on the above-mentioned problems, the inventors of this application have developed and designed a negative electrode plate system with both high energy density and high kinetics after a lot of research and experiments. The secondary battery prepared from this negative electrode plate has both high energy density and fast charging capability. More importantly, after a lot of research and experiments by the inventors, a more intuitive, effective and accurate method for evaluating the overall pore content of the plate is proposed. The negative electrode plate designed and developed according to this evaluation method has both high energy density and high kinetic characteristics, which significantly improves the insertion / extraction amount of lithium ions, as well as the migration rate of lithium ions and electrons, and ultimately significantly improves the energy density and charge and discharge rate of the battery.
[0083] [Negative electrode]
[0084] In one embodiment of the present application, the negative electrode sheet includes a current collector and a first active material layer and a second active material layer sequentially disposed on at least one surface of the current collector;
[0085] Wherein, the first active material layer includes a first negative electrode active material, and the particle size of the first negative electrode active material satisfies the relationship shown in formula (I): 0.02≤A1=(Dn10)1 / (Dv50)1≤0.2, formula (I);
[0086] Wherein, the second active material layer includes a second negative electrode active material, and the particle size of the second negative electrode active material satisfies the relationship shown in formula (II): 0.02≤A2=(Dn10)2 / (Dv50)2≤0.3, formula (II);
[0087] Furthermore, in formula (I) and formula (II), A1 and A2 satisfy 1<A2 / A1<2.5.
[0088] The inventors obtained a negative electrode plate with both high energy density and high kinetic system by regulating the particle size range of the first active substance and the second active substance, and obtained a more effective and accurate method for evaluating the overall pore content of the plate: when the particle size of the first active substance and the second active substance on the negative electrode plate simultaneously satisfies 0.02≤A1≤0.2, 0.02≤A2≤0.3 and 1<A2 / A1<2.5, the secondary battery prepared from the negative electrode plate has significantly high energy density and high charge and discharge rate.
[0089] In the evaluation formula proposed in this application, D n 10 represents the particle size corresponding to the cumulative percentage of negative electrode active material reaching 10%, D v 50 represents the particle size corresponding to the cumulative volume percentage of the negative electrode active material reaching 50%. Parameter A (A = D n 10 / D v 50) represents the filling rate between the negative electrode active material particles. The value of parameter A actually characterizes the pore occupancy in the corresponding active material layer.
[0090] After a lot of research and experiments, if the parameter A is too small (A is less than 0.02), it means that the particle size D of the small particles (or fine powder) in the negative electrode active material is n 10 and average particle size D v 50, small particles tend to fill the gaps left by large particles when preparing the slurry, which easily causes pore filling, resulting in a decrease in the pore content of the electrode, which in turn affects the liquid retention effect of the electrode and makes it impossible to achieve high-rate charge and discharge. On the contrary, if parameter A is too large (A1 is greater than 0.2 and A2 is greater than 0.3), the particle size of the active material in the active material layer is relatively uniform, and gaps are easily formed between particles. At this time, the pore content between the particles is too much, resulting in a low compaction density of the negative electrode active material. In the shell of the same size, more negative electrode sheets cannot be loaded, thereby deteriorating the energy density to a certain extent.
[0091] After a lot of research and experiments, it was found that when the parameters are 0.02≤A1≤0.2 and 0.02≤A2≤0.3, the negative electrode sheet has a reasonable pore distribution as a whole, and the secondary battery prepared in this way also has high energy density and charge and discharge rate.
[0092] In particular, the particle size of the first negative electrode active material and the second negative electrode active material of the negative electrode plate of the present application must also satisfy 1<A2 / A1<2.5, that is, to ensure that the pore content of the second active material layer is higher than that of the first active material layer. For the negative electrode plate with a fixed coating thickness, the second active material layer is in direct contact with the electrolyte. If A2 / A1<1, the pore content in the second active material layer disposed on the first active material layer is low, which increases the transmission resistance of lithium ions between the negative electrode plate and the electrolyte, which is not conducive to the overall dynamics of the negative electrode plate; if A2 / A1>2.5, the pore content of the second active material layer is too high, and it is difficult for the negative electrode plate as a whole to maintain a high compaction density, which affects the energy density of the secondary battery.
[0093] Therefore, in the formula involved in the present application, whether it is A1 controlled by the particle size of the first negative electrode active material particles, A2 controlled by the particle size of the second negative electrode active material particles, or the ratio of A2 to A1 A2 / A1, all have their own numerical ranges.
[0094] Specifically, A1 can be 0.03, 0.06, 0.08, 0.13, 0.17, or its value is within the range obtained by combining any two of the above values.
[0095] Specifically, A2 can be 0.04, 0.06, 0.08, 0.13, 0.15, 0.25, or its value is within the range obtained by combining any two of the above values.
[0096] Specifically, A2 / A1 may be 1.18, 1.5, 1.54, 2.00, 2.46, or a value within the range obtained by combining any two of the above values.
[0097] The negative electrode sheet provided by the present application has two surfaces of the negative electrode current collector opposite to each other in its thickness direction, and the first active material layer and the second active material layer are arranged on any one or both of the two opposite surfaces of the negative electrode current collector. The second active material layer covers the first active material layer, and the first active material layer and the second active material layer respectively include a first negative electrode active material and a second negative electrode active material.
[0098] The negative electrode sheet provided in the embodiment of the present application has excellent fast charging capability and energy density. During the battery charging and discharging process, the present application arranges the first active material layer and the second active material layer on the current collector to comprehensively improve the amount of lithium ion insertion / extraction, as well as the migration rate of lithium ions and electrons, so that the overall energy density and charging and discharging rate of the battery are significantly improved.
[0099] At the same time, the present application also indirectly regulates the relative porosity of the first active material layer and the second active material layer by regulating the particle size of the active material in the first active material layer and the second active material layer, and then regulates the embedding / extraction amount of lithium ions on the negative electrode sheet and the migration rate of lithium ions and electrons by changing the porosity, thereby improving the battery energy density and fast charging capability. After a lot of research and experiments, when the particle size of the first active material and the second active material on the negative electrode sheet simultaneously satisfies 0.02≤A1≤0.2, 0.02≤A2≤0.3 and 1<A2 / A1<2.5, the secondary battery prepared from the negative electrode sheet has both high energy density and high charge and discharge rate.
[0100] In one embodiment of the present application, optionally, on the negative electrode sheet of the present application, the first negative electrode active material (D v 50)1 is 12μm~20μm, and can be optionally 14μm~18μm.
[0101] In one embodiment of the present application, optionally, on the negative electrode sheet of the present application, the second negative electrode active material (D v 50)2 is 8μm~17μm, and can be optionally 10μm~15μm.
[0102] In one embodiment of the present application, optionally, the second negative electrode active material (D v 50)2 is less than the first negative electrode active material (D v 50)1, and (D v 50)1 and (D v 50)2 is not less than 3μm.
[0103] After sufficient experimental verification, the inventors found that the average particle size D of the negative electrode active material particles v The smaller 50 is, the smaller the charge exchange resistance between ions and electrons on the surface of the negative electrode active material during high-rate charge and discharge, and the faster the electrochemical reaction rate. v The smaller the value of 50, the smaller the diffusion resistance of lithium ions in the negative electrode sheet. v If 50 is too small, the specific surface area of the negative electrode active material particles will be significantly increased, which will aggravate the side reactions during the battery charging and discharging process, thereby affecting the electrochemical performance of the secondary battery.
[0104] According to the evaluation formula of the overall porosity of the negative electrode sheet of this application, by adjusting the average particle size D v The value of 50 can achieve the purpose of regulating the porosity of the negative electrode active material layer, thereby achieving the regulation of the amount of lithium ion insertion / extraction, as well as the lithium ion and electron migration rate. v 50)2 is less than the first negative electrode active material (Dv 50)1, therefore, compared with improving the fast charging capability of the battery, the first active material layer improves the overall energy density of the battery more significantly; compared with improving the energy density of the battery, the second active material layer improves the overall fast charging capability of the battery more significantly. Therefore, the present application can adjust the average particle size D of the first negative electrode active material and the second negative electrode active material particles by adjusting ... v 50, significantly improving the battery's energy density and fast charging capabilities.
[0105] After a lot of research and experiments, the inventors also found that when the first negative electrode active material (D v 50)1 is greater than the first negative electrode active material (D v 50)2, the second negative electrode active material layer has a relatively high OI value. The relatively high OI value of the second negative electrode active material layer is conducive to improving the overall bonding strength of the negative electrode sheet, while also ensuring that the second active material layer has a higher porosity and improving the fast charging capability of the negative electrode sheet.
[0106] Therefore, in the present application, whether the average particle size (D v 50) 1, and the average particle size (D v 50)2, or the difference between the two, each has its own numerical range. Specifically, (D v 50)1 can be 12 μm, 13 μm, 16 μm, or a value within the range obtained by combining any two of the above values. v 50)2 can be 8μm, 13μm, 17μm, or its value is within the range obtained by combining any two of the above values.
[0107] In one embodiment of the present application, optionally, the first negative electrode active material (D n 10) 1 is 0.5 μm to 2 μm, and can be 0.8 μm to 1.8 μm; the second negative electrode active material (D n 10)2 is 0.5μm~2μm, and can be optionally 0.8μm~1.8μm.
[0108] D n 10 represents the particle size corresponding to when the cumulative percentage of the negative electrode active material reaches 10%, which reflects the particle size of the smaller particles (or fine powder) in the negative electrode active material particles. According to the evaluation formula of the overall porosity of the negative electrode sheet of this application, when D v When 50 is a fixed value, by adjusting D n The value of 10 can achieve the purpose of regulating the porosity of the negative electrode active material layer, thereby achieving the regulation of the amount of lithium ion insertion / extraction, as well as the lithium ion and electron migration rate. n10 Within a suitable range, on the one hand, it is possible to avoid reducing the energy density of the secondary battery due to excessive overall porosity in the negative electrode plate; on the other hand, it is possible to avoid small particles (or fine powder) filling the gaps between particles and increasing the transmission resistance of lithium ions between the negative electrode plate and the electrolyte, thereby improving the fast charging capability of the secondary battery.
[0109] Therefore, in the present application, whether the first negative electrode active material particle (D n 10) 1, or the particle size of the second negative electrode active material particles (D n 10)2, each has its own numerical range. Specifically, (D n 10) 1 can be 0.5 μm, 1 μm, 2 μm, or a value within the range obtained by combining any two of the above values. n 10) 2 can be 0.5 μm, 1 μm, 2 μm, or its value is within the range obtained by combining any two of the above values.
[0110] In this application, in order to more strictly test the D n 10 and D v 50. This application adopts two testing methods, namely forward testing and reverse testing.
[0111] The forward test method is as follows:
[0112] After the first negative electrode active material and the second negative electrode active material are prepared, n 10 and D v The test of 50 is based on the test method of GB / T19077-2016 and is measured using a laser diffraction particle size distribution meter (Mastersizer3000).
[0113] The reverse test method is as follows:
[0114] The method for obtaining powder of the first active material layer and the second active material layer is as follows: the negative electrode sheet to be tested is taken, and sequentially subjected to the processes of dimethyl carbonate washing, deionized water washing, filtering, and drying, and then subjected to ion polishing cross-sectional analysis testing to obtain the thickness distribution of the first active material layer and the second active material layer.
[0115] According to the thickness distribution, first scrape the powder of the second active material layer, the scraped thickness of the second layer is controlled below 10μm, and the thickness change is monitored by a micrometer; use a strong tape to completely tear off the powder on the current collector and scrape it in the reverse direction to obtain the powder of the first active material layer.
[0116] The obtained powder was calcined in an air atmosphere at 500°C to remove the organic components, thereby obtaining the first active material layer powder 1 and the first active material layer powder 2 for testing. Then, according to the test method of GB / T19077-2016, the D of powder 1 and powder 2 were measured using a laser diffraction particle size distribution measuring instrument (Mastersizer 3000). n 10 and D v 50.
[0117] Note: For powder 1 and powder 2, since the content of the conductive agent therein is very small and the particle size of the added conductive agent is nanometer-level, in this application, the conductive agent has basically no effect on the particle size of the first negative electrode active material and the second negative electrode active material, that is, the measured particle size of powder 1 and powder 2 can be regarded as the particle size of the first negative electrode active material and the second negative electrode active material.
[0118] This conclusion has been rigorously verified by experiments, testing the particle size of the first active material and the particle size of the mixture of the first negative electrode active material and the conductive agent. The experimental process of the second negative electrode active material is the same as that of the first negative electrode active material. The test results are shown in the following table:
[0119]
[0120] In one embodiment of the present application, optionally, the thickness T1 of the first active material layer is 20 to 60 μm, and optionally 25 to 40 μm.
[0121] The first active material layer on the negative electrode sheet provided in the present application is mainly used to improve the overall energy density of the battery, so its suitable thickness range is conducive to improving the overall power durability of the battery. Optionally, the first active material layer T1 can be 20μm, 30μm, or 60μm.
[0122] In one embodiment of the present application, optionally, the thickness T2 of the second active material layer is 25 to 70 μm, and optionally 30 to 45 μm.
[0123] The negative electrode sheet provided in the present application has a second active material layer thereon which is mainly used to increase the overall porosity of the negative electrode sheet, thereby increasing the migration rate of lithium ions and electrons. Therefore, its suitable thickness range is conducive to increasing the overall charge and discharge rate of the battery and improving the fast charging capability of the battery. Optionally, the second active material layer T2 can be 25μm, 35μm, or 70μm.
[0124] In one embodiment of the present application, optionally, the thickness T2 of the second active material layer is not less than the thickness T1 of the first active material layer.
[0125] In one embodiment of the present application, optionally, a ratio T2 / T1 of a thickness T2 of the second active material layer to a thickness T1 of the first active material layer is 1.1 to 2.4. Optionally, T2 / T1 may be 1.17 or 2.33.
[0126] The negative electrode plate of the present application has a second active material layer thereon that is in direct contact with the electrolyte. Therefore, in the present application, by regulating the particle size of each active material layer, the second active material layer with a larger porosity ratio is used as a fast-charging layer that significantly improves the overall charge and discharge rate of the battery, and the first active material layer with a larger porosity ratio is used as an energy layer that significantly improves the overall energy density of the battery, thereby comprehensively improving the overall energy density and charge and discharge rate of the secondary battery. Therefore, if the thickness T2 of the second active material layer is less than the thickness T1 of the first active material layer, the overall pore content of the plate is reduced, and the high-rate charging capacity becomes worse; if the thickness of the second layer of the plate is much greater than the thickness of the first layer of the plate, it significantly affects the overall compaction density of the plate, and worsens the overall energy density of the secondary battery. Therefore, for the first active material layer and the second active material layer, the thickness T2 of the second active material layer is not less than the thickness T1 of the first active material layer.
[0127] In one embodiment of the present application, optionally, the product of T2 / T1 and A2 / A1 satisfies: 1.1≤(T2 / T1)×(A2 / A1)≤2.9. Optionally, (T2 / T1)×(A2 / A1) can be 1.38, 1.44, 2.33, or 2.87.
[0128] After a lot of research and experiments, under the condition that A2 / A1 is a certain fixed value, if the ratio of T2 / T1 is too high, the overall pore content of the pole piece is too high, the compaction density is reduced, and the overall energy density of the battery is reduced. When the thickness of the second active material layer T2 is too large, it also has an adverse effect on the fast charging capability; under the condition that T2 / T1 is a certain fixed value, if the ratio of A2 / A1 is too high, the overall pore content of the pole piece is too high, the compaction density is reduced, and the overall energy density of the battery is reduced. Therefore, the parameter (T2 / T1)×(A2 / A1) can actually characterize the relative size of the thickness of the first active material layer and the second active material layer and the relative size of their porosity. The relationship affects the battery performance. When the product of T2 / T1 and A2 / A1 satisfies: 1.1≤(T2 / T1)×(A2 / A1)≤2.9, the thickness distribution of the negative pole piece is reasonable as a whole, the pore distribution is reasonable, and the battery has both high energy density and fast charging performance.
[0129] In one embodiment of the present application, optionally, the first negative electrode active material includes graphite, and optionally the first negative electrode active material is composed of pure graphite; and / or, the second negative electrode active material includes graphite and silicon, and optionally the second negative electrode active material is composed of graphite and silicon.
[0130] In one embodiment of the present application, optionally, in the second negative electrode active material, the content of silicon converted into silicon 2 oxide accounts for 1 to 20% of the second negative electrode active material, and optionally 2 to 15% by mass.
[0131] The first negative electrode active material contains graphite, and the first active material layer has a low porosity content, which helps to improve the overall compaction performance of the electrode sheet and increase the energy density of the battery.
[0132] The negative electrode plate provided in the present application has a high pore content in the second active material layer, which is not conducive to the improvement of the compaction density of the second negative electrode active material to a certain extent. Distributing silicon in the second active material layer can significantly increase the gram capacity of the second active material layer, make up for the energy density lost by the second active material layer due to more pores, so that the battery can embed or extract more and faster lithium ions during high-rate charging and discharging, and the overall fast charging capability and power durability of the battery can be significantly improved. However, excessive silicon will cause rapid decay of the battery cycle life, so there is a suitable range of silicon oxide content, that is, the silicon oxide content accounts for 1 to 20% of the total content of the second negative electrode active material. Optionally, the silicon oxide content can be 1%, 8%, or 20%.
[0133] In one embodiment of the present application, optionally, the graphite in the first and second negative electrode active materials is selected from artificial graphite, and the artificial graphite is primary particles and / or secondary particles;
[0134] Optionally, the graphite in the first negative electrode active material is a primary particle, and the graphite in the second negative electrode active material is a secondary particle.
[0135] The graphite in the first negative electrode active material is composed of primary particles, and the porosity between particles is small, which helps to improve the overall compaction density of the pole piece and increase the energy density of the secondary battery. The graphite in the second negative electrode active material is secondary particles, which are agglomerated by primary particles, which helps to increase the porosity between particles, effectively improve the liquid retention capacity of the negative electrode material, provide more liquid phase carriers for the transmission of lithium ions in the negative electrode active material, increase the transmission rate of lithium ions, and thus increase the battery charge and discharge rate.
[0136] In one embodiment of the present application, optionally, a method for preparing a negative electrode sheet comprises the following steps:
[0137] Step S1: providing a first negative electrode active material, wherein the particle size of the first negative electrode active material satisfies the relationship shown in formula (I): 0.02≤A1=(Dn10)1 / (Dv50)1≤0.2, formula (I);
[0138] Step S2: preparing a slurry A containing a first negative electrode active material;
[0139] Step S3: providing a second negative electrode active material, wherein the particle size of the second negative electrode active material satisfies the relationship shown in formula (II): 0.02≤A2=(Dn10)2 / (Dv50)2≤0.3, formula (II);
[0140] Step S4: preparing a slurry B containing a second negative electrode active material;
[0141] Step S5: Apply slurry A on at least one surface of the current collector to form a first active material layer; apply slurry B on the surface of the first active material layer to form a second active material layer; then dry, cold press, slit, and die-cut to obtain a negative electrode sheet; wherein A1 and A2 satisfy 1<A2 / A1<2.5.
[0142] In one embodiment of the present application, optionally, in step S1, the preparation of the first negative electrode active material is sequentially carried out through the processes of raw material screening, shaping and grading, graphitization, and demagnetization and screening to obtain an average particle size (D v 50)1 A first negative electrode active material with a diameter of 12 μm to 20 μm.
[0143] In some embodiments of the present application, the first negative electrode active material with different particle size distributions can be obtained from commercial sources or prepared through artificial process.
[0144] The first negative electrode active material includes graphite, and the average particle size (D v 50)1 ranges from 12μm to 20μm. In order to obtain the first negative electrode active material particles with a suitable average particle size, the process generally goes through: raw material screening → shaping and grading → graphitization → demagnetization and screening.
[0145] In the raw material screening process, the raw materials used can be any raw materials that can be used to obtain the first negative electrode active material through the above process, for example, it can be one or more of pitch coke, petroleum coke and needle coke. The specific screening process is as follows: Use a mechanical crushing device to crush the raw materials to obtain a first precursor.
[0146] After a lot of experiments, the inventors found that the first precursor directly obtained by the mechanical crushing device has an appearance of mostly irregular particles with edges and corners. If it is directly used to prepare the precursor of the first negative electrode active material without shaping, it has many disadvantages: on the one hand, compared with the active material particles with rounded appearance, the irregular particles with edges and corners will deteriorate the electrochemical performance of the secondary battery; on the other hand, if the irregular particles with edges and corners are coated on the current collector, then during the winding process of the pole piece, these irregular particles with edges and corners can easily pierce the isolation film, bringing great safety hazards to the secondary battery. Therefore, shaping the first precursor can not only improve the electrochemical performance of the secondary battery, but also improve the safety performance of the battery.
[0147] The shaping process is a process of shaping irregular particles with edges and corners into relatively round particles. In some embodiments of the present application, the shaped first precursor is referred to as the second precursor.
[0148] In order to further screen out a more suitable precursor for preparing the first negative electrode active material, the second precursor is transported to an air flow classifier for classification, and the average particle size (D v 50)1 range is 13μm~17μm, (D n 10) 1 is a third precursor with a particle size of 0.5 to 2 μm.
[0149] The third precursor after shaping and classification is graphitized at a temperature of 2600-3000° C. to obtain a graphitized first negative electrode active material, namely, a fourth precursor.
[0150] The fourth precursor particles after graphitization may produce large particles and may be mixed with metal particles. Therefore, in order to remove the metal particles, they must first be treated with a demagnetization device and then screened with an ultrasonic vibration screen to finally obtain an average particle size (D v 50)1 in 12μm~20μm, (D n 10) 1 is a first negative electrode active material with a diameter of 0.5 to 2 μm. The SEM image of the first negative electrode active material is shown in FIG. Figure 1 .
[0151] In one embodiment of the present application, optionally, in step S3, the second negative electrode active material includes graphite and silicon; wherein the preparation of the graphite component is sequentially carried out through the processes of raw material screening, shaping and grading, granulation, graphitization, carbonization, and demagnetization and screening, and the preparation of silicon is carried out through the process of carbon coating; the graphite component and the silicon component are mixed to obtain an average particle size (D v 50)2 The second negative electrode active material is between 8μm and 17μm.
[0152] In some embodiments of the present application, the second negative electrode active material with different particle size distribution can be prepared by an artificial process. The graphite component used to prepare the second negative electrode active material can be obtained from commercial sources or prepared by an artificial process. The silicon precursor used to prepare the silicon component in the second negative electrode active material is obtained from commercial sources, and the silicon precursor SiO x (0.5<x<0.9) purchased from Peixian Rijinwen Silicon Materials Co., Ltd., 5μm≤D v 50≤8μm, 12μm≤Dv90≤16μm, 0.6μm≤Dn10≤1.5μm, specific surface area 0.8~2.2m 2 / g, 2V gram capacity 1500~1800mAh / g.
[0153] The second negative electrode active material includes graphite and silicon. The average particle size (D v 50)2 range is 8μm~17μm. In order to obtain the second negative electrode active material particles with suitable average particle size, the graphite therein roughly goes through the process of: raw material screening → shaping and classification → graphitization → carbonization → demagnetization and screening; in order to obtain suitable silicon, the application processes the purchased SiO x (0.5<x<0.9) for carbon coating modification.
[0154] In the raw material screening process, the raw materials used can be any raw materials that can obtain graphite through the above process, for example, it can be one or more of asphalt coke, petroleum coke and needle coke. The specific raw material screening process is as follows: Use a mechanical crushing device to crush the raw materials to obtain a first graphite precursor.
[0155] After a lot of experiments, the inventors found that the first graphite precursor directly obtained by the mechanical crushing device has an appearance of irregular particles with edges and corners. If it is directly used to prepare the precursor of the second negative electrode active material without shaping, it has many disadvantages: on the one hand, compared with the active material particles with rounded appearance, the irregular particles with edges and corners will deteriorate the electrochemical performance of the secondary battery; on the other hand, if the irregular particles with edges and corners are coated on the current collector, these irregular particles with edges and corners can easily pierce the isolation film during the winding process of the pole piece, which brings great safety hazards to the secondary battery. Therefore, shaping the second graphite precursor can not only improve the electrochemical performance of the secondary battery, but also improve the safety performance of the battery.
[0156] The shaping process is a process of shaping irregular particles with edges and corners into relatively round particles. In some embodiments of the present application, the shaped first graphite precursor is referred to as a second graphite precursor.
[0157] In order to further screen out a more suitable graphite precursor for preparing the second negative electrode active material, the second graphite precursor is classified by an airflow classification device, and the average particle size (D v 50)2 in 6~8μm, (D n 10)2 A third graphite precursor with a particle size of 0.5 to 2 μm.
[0158] The third graphite precursor after shaping and classification is mixed with asphalt in a mass ratio of 100:(5-20) and then granulated at a granulation temperature of 500-700° C. for 2-6 hours to obtain a fourth graphite precursor.
[0159] The fourth graphite precursor is graphitized at a temperature of 2600-3000° C. to obtain a fifth graphite precursor.
[0160] After a lot of experiments, the inventors found that carbon coating (i.e., carbonization process) the fifth graphite precursor can improve the electrochemical properties of the material on the one hand, and provide a stable chemical and electrochemical reaction interface for the negative electrode active material on the other hand. The specific carbonization process is as follows:
[0161] The fifth graphite precursor and the carbon coating agent are mixed in a mass ratio of 100:5-20, and then carbonized at 900-1200°C to obtain the sixth graphite precursor. The carbon coating agent used can be asphalt, resin, etc. Among them, asphalt can well modify the surface defects of graphite and greatly improve the performance of various aspects of the pole piece.
[0162] However, the carbonized sixth graphite precursor particles have different sizes and may be mixed with metal particles. Therefore, in order to remove the metal particles, they must first be treated with a demagnetization device and then screened with an ultrasonic vibration screen to finally obtain an average particle size (D v 50)2 at 8.5μm~~17.5μm, (D n 10) 2 The graphite component in the second negative electrode active material with a diameter of 0.5 to 2 μm. The SEM image of the graphite component in the second negative electrode active material is shown in FIG. Figure 2 .
[0163] The carbon coating modification process of commercially purchased silicon precursor is as follows: a CVD rotary furnace is used to deposit the silicon precursor SiO by vapor deposition using one or more hydrocarbon gases such as acetylene, methane, and ethylene as carbon sources. x (0.5<x<0.9) carbon coating treatment, heat treatment temperature 800~1000℃, heat treatment time 2~8h, carbon source gas flow rate 0.5~2L / min, carbon coating amount 2wt%~6wt%, to obtain the silicon component in the second negative electrode active material. The SEM image of the silicon component in the second negative electrode active material is shown in FIG. Figure 3 .
[0164] After obtaining the graphite component and the silicon component respectively, add the two components into a high-efficiency mixer and mix for 0.5h to 2h to obtain the average particle size (D v 50)2 in 8μm~17μm, (D n 10) 2 The second negative electrode active material with a particle size of 0.5 to 2 μm. The high-efficiency mixer may include other components except the graphite component and the silicon component. The SEM image of the second negative electrode active material is shown in FIG. Figure 4 .
[0165] In some embodiments of the present application, optionally, in step S2 and step S4, the conductive agent includes one or more of conductive carbon black, graphene, vapor-generated carbon fiber VGCF and carbon nanotubes;
[0166] Optionally, the mass addition ratio of the negative electrode active material, the conductive agent, the binder and the thickener is negative electrode active material: conductive agent: binder: thickener = 50-200: 1: 0.8-4: 0.5-1.5.
[0167] The negative electrode slurry coating is usually formed by dispersing the negative electrode active material and optional conductive agent, binder, thickener, etc. in a solvent and stirring them evenly. The solvent can be N-methylpyrrolidone (NMP) or deionized water.
[0168] Optionally, the conductive agent may be selected from one or more of conductive carbon black, graphene, vapor grown carbon fiber VGCF and carbon nanotubes.
[0169] Optionally, the binder can be selected from one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0170] Alternatively, the thickener may be sodium carboxymethylcellulose (CMC-Na).
[0171] In some embodiments of the present application, optionally, in step S4, the second negative electrode active material includes silicon and graphite, the conductive agent includes graphene or carbon nanotubes, and the added mass ratio of silicon to graphene or carbon nanotubes is 100 to 200:1.
[0172] The construction of the conductive network has an impact on maintaining the fast charging performance and cycle performance of the negative electrode. Generally speaking, the point-to-point conductive network is difficult to meet the activity retention rate of the silicon-containing negative electrode active material after cyclic expansion. Therefore, it is necessary to construct a point-to-plane or point-to-line conductive network to effectively maintain the cycle performance and fast charging performance of the second layer. Therefore, in this scheme, graphene with a two-dimensional structure or carbon nanotubes with a one-dimensional tubular structure are preferably used as the preferred conductive agent for the second active material layer.
[0173] Secondly, after a lot of research and experiments, the inventors also found that if the amount of graphene or carbon nanotube conductive agent added is too high, it will lead to the growth of electron and ion conduction paths, and will also cover the active sites of the negative electrode active material, resulting in deterioration of fast charging performance; on the contrary, if the amount added is too low, it will be difficult to maintain the excellent conductivity of the electrode, affecting the battery. In this application, when the ratio of silicon and graphene or carbon nanotube addition is 100 to 200:1, the battery can take into account both fast charging performance and cycle life.
[0174] In some embodiments of the present application, optionally, in step S5, the thickness of the first active material layer is 20 to 60 μm, and the thickness of the second active material layer is 25 to 70 μm. The second active material layer covers the first active material layer. For specific SEM images, refer to Figure 5 .
[0175] The preparation method of the negative electrode sheet provided in the present application has a simple preparation process and low raw material cost, which is conducive to large-scale industrialization. The negative electrode sheet prepared according to the method of the present application is an indispensable raw material for preparing batteries with both fast charging capability and high energy density.
[0176] In the negative electrode sheet of the present application, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by disposing a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0177] In the secondary battery of the present application, the first active material layer and the second active material layer generally contain negative electrode active materials and optional binders, optional conductive agents and other optional auxiliary agents, and are generally formed by coating and drying negative electrode slurry. The negative electrode slurry coating is generally formed by dispersing the negative electrode active materials and optional conductive agents and binders in a solvent and stirring them uniformly, and the solvent may be N-methylpyrrolidone (NMP) or deionized water.
[0178] Optionally, the conductive agent may be selected from one or more of conductive carbon black, graphene, vapor grown carbon fiber VGCF and carbon nanotubes.
[0179] Optionally, the binder can be selected from one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0180] Optionally, other optional auxiliary agents may be thickeners, such as sodium carboxymethyl cellulose (CMC-Na) and the like.
[0181] [Positive electrode]
[0182] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.
[0183] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0184] In the present application, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0185] The positive electrode film layer may also optionally include a conductive agent. However, there is no specific limitation on the type of the conductive agent, and those skilled in the art may select it according to actual needs. As an example, the conductive agent used for the positive electrode film layer may be selected from one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0186] In the present application, the positive electrode sheet can be prepared according to methods known in the art. As an example, the positive electrode active material, conductive agent and binder of the present application can be dispersed in a solvent (such as N-methylpyrrolidone (NMP)) to form a uniform positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet is obtained.
[0187] [Electrolytes]
[0188] The electrolyte plays the role of conducting ions between the positive electrode plate and the negative electrode plate. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (i.e., an electrolyte).
[0189] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0190] In some embodiments, the electrolyte salt can be selected from one or more of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalatoborate), LiBOB (lithium dioxalatoborate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorobis(oxalatophosphate)) and LiTFOP (lithium tetrafluorooxalatophosphate).
[0191] In some embodiments, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0192] In some embodiments, the electrolyte may also optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.
[0193] [Isolation film]
[0194] Secondary batteries using electrolytes and some secondary batteries using solid electrolytes also include a separator. The separator is arranged between the positive electrode plate and the negative electrode plate to play an isolating role. The present application has no particular restrictions on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected. In some embodiments, the material of the separator can be selected from one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular restrictions. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular restrictions.
[0195] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0196] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0197] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0198] In some embodiments of the present application, optionally, a secondary battery is provided, comprising the negative electrode plate of the first aspect of the present application or the negative electrode plate prepared according to the method of the second aspect of the present application.
[0199] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 7 The secondary battery 5 is a square structure as an example.
[0200] In some embodiments, reference Figure 8 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0201] In some embodiments of the present application, optionally, a battery module is provided, comprising the secondary battery of the present application.
[0202] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0203] Fig. 9 4 is an example of a battery module. Fig.10 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0204] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0205] In some embodiments of the present application, optionally, a battery pack is provided, comprising one or more of the secondary batteries of the present application or the battery modules of the present application.
[0206] In some embodiments, the battery modules of the present application may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0207] Fig.10 1 is a battery pack 1 as an example. Fig.11 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0208] In some embodiments of the present application, optionally, an electric device is provided, comprising one or more of the secondary battery, battery module or battery pack of the present application. The secondary battery, battery module or battery pack can be used as a power source for the electric device or an energy storage unit for the electric device.
[0209] Electrical devices may include but are not limited to mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0210] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0211] Fig.12 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the device for the secondary battery, a battery pack or a battery module can be used.
[0212] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and a secondary battery may be used as a power source.
[0213] Example
[0214] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0215] Example 1
[0216] [Preparation of the first negative electrode active material]
[0217] Raw material screening: putting the pitch coke into a mechanical crusher and crushing it using the mechanical crusher to obtain a first precursor;
[0218] Shaping and classification: The first precursor is shaped to obtain a second precursor with a rounder appearance. The second precursor is transported to the airflow classifier for classification, and the average particle size (D v 50)1 is 17μm, (D n 10)1 is a third precursor with a thickness of 1 μm.
[0219] Graphitization: The third precursor after shaping and classification is graphitized at a treatment temperature of 3000 to obtain a fourth precursor.
[0220] Demagnetization and screening: The fourth precursor is demagnetized using a demagnetizer, and the large particles produced after graphitization are removed using an ultrasonic vibration screen to obtain the first negative electrode active material, the average particle size of which (D v 50)1 is 16μm, (D n 10)1 is 1μm.
[0221]
Preparation of the second negative electrode active material
[0222] Preparation of graphite component in the second negative electrode active material
[0223] Raw material screening: using a mechanical crusher to crush petroleum coke to obtain the first graphite precursor;
[0224] Shaping and classification: The first graphite precursor is shaped to obtain a second graphite precursor with a relatively rounded appearance. The second graphite precursor is transported to the airflow classifier for classification, and the average particle size (D v 50)2 is 7μm, (D n 10)2 is a third graphite precursor with a particle size of 0.8 μm.
[0225] Granulation: The third graphite precursor after shaping and classification and asphalt were mixed in a mass ratio of 100:12 and granulated at a temperature of 600°C for 2 hours to obtain an average particle size (D v 50)2 is 13μm, (Dn 10 )2 is a fourth graphite precursor with a diameter of 1 μm.
[0226] Graphitization: The fourth graphite precursor is graphitized at a temperature of 2800° C. to obtain a fifth graphite precursor.
[0227] Carbonization: The fifth graphite precursor and asphalt are mixed in a mass ratio of 100:6, and then carbonized at a carbonization temperature of 1150 to obtain a sixth graphite precursor.
[0228] Demagnetization and screening: The sixth graphite precursor is demagnetized using a demagnetizer, and the large particles produced after carbonization are removed using an ultrasonic vibration screen to obtain the second negative electrode active material, the average particle size of which (D v 50)2 is 13μm, (D n 10)2 is 1μm.
[0229] Preparation of silicon component in the second negative electrode active material
[0230] The silicon precursor SiO was deposited by vapor deposition using acetylene as the carbon source in a CVD rotary furnace. x (0.5<x<0.9) Carbon coating treatment was carried out, the heat treatment temperature was 900, the heat treatment time was 4h, the carbon source gas flow rate was 1L / min, and the carbon coating amount was 4wt% to obtain the silicon component in the second negative electrode active material.
[0231] Preparation of the second negative electrode active material
[0232] After obtaining the appropriate graphite component and the appropriate silicon component, the two are added into a high-efficiency mixer and mixed for 1 hour to obtain the second negative electrode active material, the average particle size of which (D v 50)2 is 13μm, (D n 10)2 is 1μm.
[0233]
Preparation of negative electrode sheet
[0234] The first negative electrode active material, conductive carbon black, thickener sodium carboxymethyl cellulose, and binder styrene-butadiene rubber were mixed in a mass ratio of 96.2:1.0:1.0:1.8, and then deionized water was added and stirred to a uniform state under the action of a vacuum mixer to obtain a negative electrode slurry A with a solid content of 52%. The negative electrode slurry A was evenly coated on the negative electrode current collector copper foil and dried at 85 to obtain a negative electrode sheet coated with the first negative electrode active material.
[0235] The second negative electrode active material, carbon nanotubes, thickener sodium carboxymethyl cellulose, and binder styrene butadiene rubber are mixed in a mass ratio of 96.2:1.0:1.0:1.8, and then deionized water is added, and stirred to a uniform state under the action of a vacuum mixer to obtain a negative electrode slurry B with a solid content of 52%; the negative electrode slurry B is evenly coated on the first negative electrode film layer and dried at 85.
[0236] The negative electrode sheet coated with the first negative electrode active material and the second negative electrode active material is subjected to the processes of cold pressing, trimming, stripping, and cutting, and then dried for 12 hours under a vacuum condition of 120°C to obtain the target negative electrode sheet. According to the test, the thickness T1 of the first active material layer is 30 μm, and the thickness T2 of the second active material layer is 35 μm.
[0237] The only difference between Examples 2 to 13 and Comparative Examples 1 to 6 and Example 1 is that the particle size (D v 50)1, (D n 10) 1, and the particle size of the second negative electrode active material (D v 50)2、(D n 10)2 has differences in specific values. For specific values, please see Table 1.
[0238] The difference between Examples 14 to 21 and Example 1 is only the difference in the values of the first active material layer thickness T1 and the first active material layer thickness T2 corresponding to each example. The specific values are shown in Table 2.
[0239] The only difference between Example 22 and Example 1 is the difference in the specific values of the parameters (T2 / T1)×(A2 / A1) corresponding to each example. The specific values are detailed in Table 3.
[0240] The only difference between Examples 23 to 26 and Example 1 is the difference in the specific values of the silicon oxide content corresponding to each example. The specific values are shown in Table 4.
[0241]
Preparation of positive electrode
[0242] The positive electrode NCM ternary material, the conductive agent Super P, and the binder polyvinylidene fluoride were mixed in a mass ratio of 97:1.5:1.5, and the solvent N-methylpyrrolidone was added, and the system was stirred in a vacuum until it was uniform to obtain a positive electrode slurry with a solid content of 77wt%. The positive electrode slurry was evenly coated on the positive electrode current collector aluminum foil and dried at 85. After cold pressing, trimming, striping, and cutting, it was continued to be dried under vacuum conditions of 85 for 4h to obtain a positive electrode sheet.
[0243]
Preparation of electrolyte
[0244] Ethylene carbonate, ethyl methyl carbonate and diethyl carbonate are prepared into a mixed solution in a volume ratio of 20:20:60, and then fully dried lithium salt is dissolved in the mixed solution, and then 10wt% of fluoroethylene carbonate additive is added and mixed evenly to obtain an electrolyte. The concentration of the lithium salt is 1 mol / L. The entire operation process is carried out in an argon atmosphere glove box with a water content of less than 10ppm.
[0245]
Isolation film
[0246] Preparation of isolation film
[0247] A polyethylene film with a thickness of 12 μm is used as the substrate, and a 2 μm coating is applied on the surface as an isolation film.
[0248]
Preparation of secondary batteries
[0249] The negative electrode sheets, separators, and positive electrode sheets in Examples 1 to 21 and Comparative Examples 1 to 6 are stacked in order, with the separator between the positive and negative electrode sheets, and then wound into a bare cell. The bare cell is welded with pole ears, and the bare cell is placed in an aluminum shell, and baked at 80 degrees to remove water, and then the electrolyte is injected and sealed to obtain an uncharged secondary battery. The uncharged secondary battery is then subjected to the processes of standing, hot and cold pressing, formation, shaping, and capacity testing to obtain a secondary battery product. The battery capacity shipped is 50% SOC.
[0250] [Negative electrode parameter test]
[0251] 1. Particle size test of the first negative electrode active material and the second negative electrode active material
[0252] According to the GB / T19077-2016 test method, a laser diffraction particle size distribution measuring instrument (Mastersizer 3000) was used to measure the particle sizes of the powders 1 and 2 corresponding to all the embodiments and comparative examples.
[0253] 2. Thickness test of the first active material layer and the second active material layer
[0254] The negative electrode sheets corresponding to all the embodiments and comparative examples were cut into a size of 6 mm × 6 mm, and polished with an ion polisher from Leica, Germany, at 7.5 KV for 90 min. Then, the thickness of each layer was measured using a scanning electron microscope (Zeiss Sigma300) according to the JY / T010-1996 standard.
[0255]
Battery performance test
[0256] 1. Energy density test
[0257] At 25°C, the batteries prepared in the examples and comparative examples were fully discharged at 1C, then fully charged at 1C, and fully discharged at 1C, and the actual discharge energy at this time was recorded; the batteries were weighed using an electronic balance at 25°C. The ratio of the actual discharge energy D / Wh of the battery at 1C to the battery weight m / kg is the actual energy density E of the battery, E=D / m.
[0258] 2. Fast charging performance test
[0259] At 25°C, the secondary battery used to test the fast charging performance was charged at a constant current of 0.33C (i.e., the current value that completely discharges the theoretical capacity within 1 hour) to a charging cut-off voltage of 4.25V, and then charged at a constant voltage to a current of 0.05C. After standing for 5 minutes, it was discharged at a constant current of 0.33C to a discharge cut-off voltage V2, and its actual capacity was recorded as C0.
[0260] Then the battery is charged with constant current of 0.3C0, 0.5C0, 1.0C0, 1.5C0, 2.0C, 2.5C0 in sequence to the full battery charge cut-off voltage of 4.25V or 0V negative electrode cut-off potential (whichever is reached first), and after each charge is completed, it needs to be discharged with 1C0 to the full battery discharge cut-off voltage of 2.8V. Record the corresponding negative electrode potential when charged to 10% SOC, 20% SOC, 30% SOC, ..., 80% SOC at different charge rates.
[0261] Draw the rate-negative electrode potential curve under different SOC states (refer to Figure 6 ), after linear fitting, the charge rate (C = -intercept / slope) corresponding to the negative electrode potential of 0 V under different SOC states is obtained. The charge rate is the charge window under the SOC state. The charge windows under 10% SOC, 20% SOC, 30% SOC, ..., 80% SOC are respectively recorded as C 10%SOC , C 20%SOC , C 30%SOC , C 40%SOC , C 50%SOC , C 60%SOC , C 70%SOC , C 80%SOC According to the formula (60 / C 10%SOC +60 / C 20%SOC +60 / C 30%SOC +60 / C 40%SOC +60 / C 50%SOC +60 / C 60%SOC +60 / C 70%SOC +60 / C 80%SOC)×10% to calculate the charging time T (min) of the battery from 10% SOC to 80% SOC. The shorter the time, the stronger the fast charging capability of the battery. Taking Example 5 as an example, the rate-negative electrode potential curves under different SOC states are as follows: Figure X .
[0262] From the fitting formula of each curve, we can know that: C 10%SOC , C 20%SOC , C 30%SOC , C 40%SOC , C 50%SOC , C 60%SOC , C 70%SOC , C 80%SOC The values are 9.74, 5.34, 4.08, 3.11, 2.49, 2.23, 1.88 and 1.57 respectively. The charging time T = (60 / 9.74 + 60 / 5.34 + 60 / 4.08 + / 60 / 3.11 + 60 / 2.49 + 60 / 2.49 + 60 / 2.23 + 60 / 1.88 + 60 / 1.57) × 10% = 17.3 min.
[0263] Table 1: Effect of particle size of the first negative electrode active material and the second negative electrode active material on battery performance
[0264]
[0265]
[0266] Table 2: Effect of the thickness of the first active material layer and the second active material layer on battery performance parameters
[0267]
[0268] Table 3: Effect of (T2 / T1)×(A2 / A1) on battery performance parameters
[0269]
[0270] Table 4: Effect of silicon oxide content in the second negative electrode active material on battery performance parameters
[0271]
[0272]
[0273] [Analysis of the influence of particle size on battery performance]
[0274] It can be seen from Table 1 that the values of parameters A1, A2 and A2 / A1 corresponding to Examples 1 to 13 are all within the scope of this application. It can be seen from the experimental data that the secondary batteries corresponding to Examples 1 to 13 have high energy density, and the fast charging time is less than that of Comparative Examples 1 to 6, all within 20 minutes. Therefore, when the particle sizes of the first active material and the second active material on the negative electrode sheet simultaneously satisfy 0.02≤A1≤0.2, 0.02≤A2≤0.3 and 1<A2 / A1<2.5, the secondary battery prepared from the negative electrode sheet has both high energy density and fast charging performance.
[0275] Although Example 12 and Example 13 satisfy 0.02≤A1≤0.2, 0.02≤A2≤0.3 and 1<A2 / A1<2.5, the corresponding average particle size (Dv50) 1 of the first negative electrode active material is relatively large (greater than 20μm) and the average particle size (Dv50) 2 of the second negative electrode active material is relatively small (less than 8μm), which correspondingly leads to a lower porosity of the first active material layer (low lithium ion migration rate of the first active material layer) and a higher porosity of the second active material layer (low compaction density of the second active material layer material), resulting in a lower energy density of the corresponding secondary battery, which has a certain impact on the fast charging performance of the battery.
[0276] Compared with the embodiment, in Comparative Example 1, the average particle size (Dv50) 1 of the first negative electrode active material is smaller (less than 12 μm), and the corresponding A1 is greater than A2, and A2 / A1 < 1, indicating that in this case, the compaction density of the first negative electrode active material in the first active material layer is low, and the porosity is greater than that of the second active material layer, which makes the overall gram capacity of the negative electrode sheet material low and has a certain impact on the overall fast charging performance of the battery. Therefore, the energy density of the secondary battery corresponding to Comparative Example 1 is relatively low.
[0277] Compared with the embodiment, in Comparative Example 2, the average particle size (Dv50)2 of the second negative electrode active material is larger (greater than 17 μm). At this time, the corresponding A1 is greater than A2, and A2 / A1 is less than 1, which means that in this case, the porosity of the second active material layer is low, and the diffusion resistance of lithium ions and electrons in the second active material layer is large. For the secondary battery, the internal resistance of the battery increases accordingly. Therefore, the fast charging time is significantly longer than that of the embodiment, and the battery fast charging performance is poor.
[0278] Compared with the embodiment, in comparative example 3, the (D n 10) 1 is too small (less than 0.5 μm), which makes the porosity in the first active material layer low, affecting the overall pore content of the electrode, and thus resulting in poor fast charging performance. On the contrary, in Comparative Example 5, the (D n10) 1 is too large (greater than 2 μm), which results in a high porosity in the first active material layer and a corresponding decrease in the gram capacity of the material, which in turn leads to a low overall compaction density of the electrode, thereby reducing the battery energy density.
[0279] Compared with the embodiment, in Comparative Example 4, the second negative electrode active material (D n 10)2 is too large (greater than 2μm), and A2 / A1 is also greater than 2.5, which indicates that the porosity in the second active material layer is too high and the compaction density of the second negative electrode active material is low, resulting in the low overall energy density of the battery and also having a certain impact on the fast charging capability.
[0280] Compared with the embodiment, in Comparative Example 6, the second negative electrode active material (D n 10)2 is low (less than 0.5 μm), and A2 / A1 is also less than 1, which indicates that the porosity in the second active material layer is too low and the diffusion resistance of lithium ions in the second active material layer is large, resulting in poor fast charging performance.
[0281] [Analysis of the influence of active material layer thickness on battery performance parameters]
[0282] As can be seen from Table 2, for Example 1 and Examples 14 to 17, the thickness T1 of the first active material layer and the thickness T2 of the second active material layer are both within the range required by this application. Although the increase in the overall thickness of Example 15 and Example 16 has a slight impact on the fast charging performance of the battery, the overall performance can still be maintained within 20 minutes. In addition, the ratio of the thickness T2 of the second active material layer to the thickness T1 of the first active material layer is also within the range required by this application, and the secondary battery as a whole has excellent energy density and fast charging performance.
[0283] For Example 18, the thickness of the first active material layer is too large (T1 is greater than 60μm), which is greater than the thickness of the second active material layer, and T2 / T1 is less than 1.1, indicating that the second active material layer with higher porosity has low porosity, so the pole piece has a lower pore content as a whole, and the fast charging performance is significantly reduced. In Example 19, the thickness of the second active material layer is relatively thin relative to the first active material layer, and T2 / T1 is less than 1.1, so the overall pore content of the pole piece is low, and the fast charging capability is slightly deteriorated. In Example 20, although the T2 / T1 ratio is appropriate, the first active material layer is thin, which shows that the contribution of the first active material layer with a higher material capacity to the battery energy density is reduced, and therefore has a certain impact on the energy density of the secondary battery. In Example 21, the thickness of the first active material layer is moderate, but the thickness of the second active material layer with higher porosity is thick (T2 is greater than 70μm), and T2 / T1 is too large, so the overall compaction density of the pole piece is low, and the energy density is significantly reduced.
[0284] [Analysis of the influence of (T2 / T1)×(A2 / A1) parameters on battery performance]
[0285] It can be seen from Table 3 that for Examples 1 and 3 and 15, the numerical range of (T2 / T1)×(A2 / A1) is within the range required by the present application, that is, the relative thickness of the two layers of the negative electrode plate and the relative porosity content of the two layers meet the requirements of the present application, so the secondary battery has excellent energy density and fast charging performance as a whole.
[0286] For Example 15, the value of the parameter (T2 / T1)×(A2 / A1) is too high (higher than 2.9), indicating that the overall compaction density of the electrode is poor and the overall energy density of the battery is poor.
[0287] [Analysis of the influence of silicon oxide content on battery performance]
[0288] As can be seen from Table 4, in Example 1, the silicon content is moderate, and the pole piece has both high energy density and fast charging capability; in Example 23, the silicon oxide content in the second negative electrode active material is lower than that in Example 1, so the energy density is low, but the fast charging capability is good. In Example 24, the silicon oxide content in the second negative electrode active material is higher than that in Example 1, and the energy density is higher, but it has a certain impact on the fast charging capability. However, when the silicon oxide content is within the scope of this application, the secondary battery in the embodiment as a whole takes into account both high energy density and fast charging performance.
[0289] For Example 25, the second negative electrode active material does not contain silicon components but only pure graphite components, so the energy density of the secondary battery is low, but it has almost no effect on the fast charging performance. In Example 26, the silicon oxide content in the second negative electrode active material is too high (higher than 20%), indicating that excessive silicon will deteriorate the migration rate of lithium ions and electrons in the second active material layer. Therefore, when the silicon oxide content in the second negative electrode active material is high, the energy density of the secondary battery is high, but its fast charging performance is poor.
[0290] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely illustrative, and embodiments having substantially the same structure as the technical idea and exerting the same effects within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, within the scope of the subject matter of the present application, various modifications that can be thought of by those skilled in the art to the embodiments, and other methods of combining some of the constituent elements in the embodiments to construct are also included in the scope of the present application.
Claims
1. A negative electrode plate, characterized in that: It includes a current collector and a first active material layer and a second active material layer sequentially disposed on at least one surface of the current collector; The first active material layer includes a first negative electrode active material, and the particle size of the first negative electrode active material satisfies the relationship shown in formula (I): 0.02≤A1=(D n 10)1 / (D v 50)1≤0.2, formula (I); The second active material layer includes a second negative electrode active material, and the particle size of the second negative electrode active material satisfies the relationship shown in formula (II): 0.02≤A2=(D n 10)2 / (D v 50)2≤0.3, formula (II); Furthermore, in the formula (I) and the formula (II), A1 and A2 satisfy 1 <A2 / A1<2.5。 2. The negative electrode sheet according to claim 1, characterized in that: The first negative electrode active material has a (D v 50)1 is 12μm~20μm.
3. The negative electrode sheet according to claim 2, characterized in that: The first negative electrode active material has a (D v 50)1 is 14μm~18μm.
4. The negative electrode sheet according to claim 1, characterized in that: The second negative electrode active material (D v 50)2 is 8μm~17μm.
5. The negative electrode sheet according to claim 4, characterized in that: The second negative electrode active material (D v 50)2 is 10μm~15μm.
6. The negative electrode sheet according to any one of claims 2 to 5, characterized in that: The first negative electrode active material (D n 10) 1 is 0.5 μm to 2 μm; The second negative electrode active material (D n 10)2 is 0.5μm~2μm.
7. The negative electrode sheet according to claim 6, characterized in that: The first negative electrode active material (D n 10)1 is 0.8μm~1.8μm.
8. The negative electrode sheet according to claim 6, characterized in that: The second negative electrode active material (D n 10)2 is 0.8μm~1.8μm.
9. The negative electrode sheet according to any one of claims 2 to 5, characterized in that: The second negative electrode active material (D v 50)2 is less than (D v 50)1, and (D v 50)1 and (D v 50)2 is not less than 3μm.
10. The negative electrode sheet according to claim 1, characterized in that: The thickness T1 of the first active material layer is 20 to 60 μm.
11. The negative electrode sheet according to claim 10, characterized in that: The thickness T1 of the first active material layer is 25 to 40 μm.
12. The negative electrode sheet according to claim 1, characterized in that: The thickness T2 of the second active material layer is 25 to 70 μm.
13. The negative electrode sheet according to claim 12, characterized in that: The thickness T2 of the second active material layer is 30 to 45 μm.
14. The negative electrode sheet according to claim 12, characterized in that: The thickness T2 of the second active material layer is not less than the thickness T1 of the first active material layer.
15. The negative electrode sheet according to any one of claims 12 to 14, characterized in that: A ratio T2 / T1 of a thickness T2 of the second active material layer to a thickness T1 of the first active material layer is 1.1 to 2.
4.
16. The negative electrode sheet according to claim 15, characterized in that: The product of T2 / T1 and A2 / A1 satisfies: 1.1<(T2 / T1)×(A2 / A1)≤2.
9.
17. The negative electrode sheet according to claim 16, characterized in that: The first negative electrode active material includes graphite; and / or, The second negative electrode active material includes graphite and silicon.
18. The negative electrode sheet according to claim 17, characterized in that: The first negative electrode active material is composed of graphite.
19. The negative electrode sheet according to claim 17, characterized in that: The second negative electrode active material consists of graphite and silicon.
20. The negative electrode plate according to claim 17, characterized in that: In the second negative electrode active material, the content of the silicon converted into silicon 2 oxide accounts for 1 to 20% of the second negative electrode active material in terms of mass percentage.
21. The negative electrode sheet according to claim 20, characterized in that: The content of the silicon converted into silicon monoxide accounts for 2 to 15% of the second negative electrode active material.
22. The negative electrode plate according to claim 17, characterized in that: The graphite in the first and second negative electrode active materials is selected from artificial graphite, and the artificial graphite is primary particles and / or secondary particles.
23. The negative electrode sheet according to claim 22, characterized in that: The graphite in the first negative electrode active material is a primary particle, and the graphite in the second negative electrode active material is a secondary particle.
24. A method for preparing a negative electrode sheet, characterized in that: The method comprises the following steps: Step S1: providing a first negative electrode active material, wherein the particle size of the first negative electrode active material satisfies the relationship shown in formula (I): 0.02≤A1=(D n 10)1 / (D v 50)1≤0.2, formula (I); Step S2: preparing a slurry A containing the first negative electrode active material; Step S3: providing a second negative electrode active material, wherein the particle size of the second negative electrode active material satisfies the relationship shown in formula (II): 0.02≤A2=(D n 10)2 / (D v 50)2≤0.3, formula (II); Step S4: preparing a slurry B containing the second negative electrode active material; Step S5: applying the slurry A on at least one surface of the current collector to form a first active material layer; applying the slurry B on the surface of the first active material layer to form a second active material layer; and then drying, cold pressing, slitting, and die-cutting to obtain the negative electrode sheet; Wherein, A1 and A2 satisfy 1 <A2 / A1<2.5。 25. The method for preparing a negative electrode sheet according to claim 24, characterized in that: In step S1, the first negative electrode active material is prepared by sequentially undergoing the processes of raw material screening, shaping and grading, graphitization, and demagnetization and screening to obtain an average particle size (D v 50)1 in 12μm~20μm, (D n 10) A first negative electrode active material having a thickness of 0.5 μm to 2 μm.
26. The method for preparing a negative electrode sheet according to claim 24, characterized in that: In the step S3, the second negative electrode active material includes graphite and silicon; The preparation of graphite is sequentially carried out through the processes of raw material screening, shaping and grading, granulation, graphitization, carbonization, and demagnetization and screening, and the preparation of silicon is carried out through the process of carbon coating; The graphite and the silicon are mixed to obtain an average particle size (D v 50)2 in 8μm~17μm, (D n 10) A second negative electrode active material having a diameter of 0.5 μm to 2 μm.
27. The method for preparing a negative electrode sheet according to claim 24, characterized in that: In the step S2 and the step S4, the slurry B and the slurry A respectively further include a conductive agent, and the conductive agent includes one or more of conductive carbon black, graphene, vapor-generated carbon fiber VGCF and carbon nanotubes.
28. The method for preparing a negative electrode sheet according to claim 27, characterized in that: The mass ratio of the negative electrode active material, the conductive agent, the binder and the thickener added is negative electrode active material: conductive agent: binder: thickener = 50-200: 1: 0.8-4: 0.5-1.
5.
29. The method for preparing a negative electrode sheet according to claim 24, characterized in that: In step S4, the slurry B further includes a conductive agent, the second negative electrode active material includes silicon and graphite, and the conductive agent includes graphene or carbon nanotubes.
30. The method for preparing a negative electrode sheet according to claim 29, characterized in that: The mass addition ratio of the silicon to the graphene or the silicon to the carbon nanotube is 100-200:
1.
31. A secondary battery, characterized in that: The negative electrode sheet is the negative electrode sheet according to any one of claims 1 to 23 or the negative electrode sheet prepared by the method according to any one of claims 24 to 30.
32. A battery module, characterized in that: Includes the secondary battery as claimed in claim 31.
33. A battery pack, characterized in that: The invention comprises one or more of the secondary battery according to claim 31 or the battery module according to claim 32.
34. An electrical device, characterized in that: It comprises one or more of the secondary battery of claim 31, the battery module of claim 32 or the battery pack of claim 33, and the secondary battery, the battery module or the battery pack is used as a power source for the electrical device or an energy storage unit for the electrical device.
Citation Information
Patent Citations
Secondary battery
CN109449446A
Negative pole sheet, preparation method thereof, lithium ion battery, preparation method of lithium ion battery and application of lithium ion battery
CN110660965A